Pengaruh Electronic Word Of Mouth (E-WOM) Dari Youtube Beauty Vlogger Terhadap Keputusan Pembelian Produk Kosmetik Wardah Melalui Brand Image (Studi Pada Mahasiswi Fakultas Ekonomi dan Bisnis Universitas Trunojoyo Madura) - Chasanah, Ismayanti; Chrismardani, Yustina (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This research discusses the problems with one of Indonesia's local cosmetic products, namely Wardah cosmetic products. The purpose of this study is to explain the effect of Electronic Word Of Mouth (E-Wom) on the decision to purchase Wardah cosmetic products, to explain the effect of Electronic Word Of Mouth (E-Wom) on the Brand Image of Wardah cosmetic products, to explain the effect of Brand Image on purchasing decisions Wardah cosmetic products, to explain the influence of Electronic Word Of Mouth (E-Wom) on purchasing decisions for Wardah cosmetic products through Brand Image. This study used a quantitative approach using the method of path analysis (path analysis), with a total of 96 respondents. The results of this study are (1) Electronic Word Of Mouth has no significant effect on purchasing decisions (2) Electronic Word Of Mouth has a significant effect on brand image (3) Brand Image has a significant effect on purchasing decisions (4) Electronic Word Of Mouth has a significant on purchase decision through brand image.